Evaluation of Agronomic Management Practices on Farmers’ Fields under Rice-Wheat Cropping System in Northern India - Dinesh Kumar Singh; Purushottam Kumar; A. K. Bhardwaj (International Journal of Agronomy)
Rice (Oryza sativa L.)-wheat (Triticum aestivum L. emend. Fiori and Paol.) is the most important two crops a year intensive rice based cropping system of Asia. Agronomic management is the most important input for getting potential yield and high net returns in any crop or crop sequence. Most of the farmers used to grow old varieties of rice and wheat without any row arrangement. Fertilization is mainly limited to nitrogenous fertilizer only. Therefore, the present study was undertaken to find out the effect of different agronomic management practices on productivity and economics of rice-wheat system at farmers’ fields. Inclusion of improved variety in rice and wheat incurred additional cost of $52/ha and provided additional return of $101/ha, whereas sowing/transplanting of rice and wheat in lines incurred additional cost of $30/ha and resulted in additional returns of $146/ha. Balanced fertilization incurred additional cost of $38 over the imbalanced fertilization and provided additional returns of $180/ha. Recommended package of practices (improved variety, line sowing/transplanting and balanced fertilization) incurred additional cost of cultivation of $120/ha over the farmers’ practice and achieved additional net returns of $426/ha.